Detection of skin cancer using Convolutional neural network - Ahsan, Abu Sa-adat Mohamed Moon-Im Al; Alif, Shadman Monsur; Kibria, Junaid Bin; Gomes, Prince Elvis (Brac University, 2020)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science, 2019.